1993
DOI: 10.1179/mst.1993.9.10.907
|View full text |Cite
|
Sign up to set email alerts
|

Influence of deformation induced ferrite, grain boundary sliding, and dynamic recrystallisation on hot ductility of 0·1–0·75%C steels

Abstract: The influence ofC on hot ductility in the temperature range 600-1000°C has been examinedfor three C contents (0·1,0'4, and 0·75 wt-%). Using a strain rate of 3 x 10-3 S-l, tensile specimens were heated to 1330°C before cooling to the test temperature. For the 0·4%C steel, two further strain rates of 3 x 10-2 and 3 x 10-4 S-l were examined. At the strain rate of 3 x 10-3 S-l, increasing the C content shifted the low ductility trough to lower temperatures in accordance with the trough being controlled by the y-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 9 publications
1
38
0
3
Order By: Relevance
“…When the concentration of the strain in the ferrite film is the only embrittlement mechanism acting, the ductility rebounds at temperatures below the Ar 3 , when a higher amount of ferrite transforms homogeneously in the matrix, and at temperatures above the Ae 3 , since this is the highest temperature at which ferrite can form induced by deformation. 24,25) For the steels in Table 1, even though they are C-Mn steels, the rebound in the hot ductility at high temperatures takes place well above the calculated Ae 3 for any of the reheating conditions or in-situ melting. This means that other mechanisms appart from the concentration of the strain in the ferrite film are contributing to deteriorate the ductility of both steels in the austenite range.…”
Section: Overview Of the Mechanisms Of Hot Ductilitymentioning
confidence: 99%
“…When the concentration of the strain in the ferrite film is the only embrittlement mechanism acting, the ductility rebounds at temperatures below the Ar 3 , when a higher amount of ferrite transforms homogeneously in the matrix, and at temperatures above the Ae 3 , since this is the highest temperature at which ferrite can form induced by deformation. 24,25) For the steels in Table 1, even though they are C-Mn steels, the rebound in the hot ductility at high temperatures takes place well above the calculated Ae 3 for any of the reheating conditions or in-situ melting. This means that other mechanisms appart from the concentration of the strain in the ferrite film are contributing to deteriorate the ductility of both steels in the austenite range.…”
Section: Overview Of the Mechanisms Of Hot Ductilitymentioning
confidence: 99%
“…[3] It is not surprising, therefore, that the HDH region has been observed to coincide with the onset of dynamic recrystallization in many studies. [41,56,57] However, there are numerous instances where dynamic recrystallization has been observed throughout ail, or part of the region of embrittlement. [3,54,56] Such results demonstrate that it is indeed grain boundary migration that is the important event, dynamic recrystallization being an effective means by which this can be achieved.…”
Section: Grain Boundary Slidingmentioning
confidence: 99%
“…[39] It has been aIso shown that this ferrite film can be induced by deformation. [40][41][42][43][44][45] untransformed austenite…”
Section: Ferrite At Grain Boundariesmentioning
confidence: 99%
“…1,12) Figure 8 shows the microstructures of a specimen after a tensile test at higher temperature. A fully recrystallized structure was revealed for specimen TH5 tested at 850°C (Fig.…”
Section: Ductility Recoverymentioning
confidence: 99%